The Adaptation Tajur Village Traditional House of Vernacular Architecture to Local Climate - Shabirah, Fakhitah; Octaviani, Astrid; Daming, Takdir; Permana, Asep Yudi (Proceeding of International Joint Conference on UNESA, 2025)
Sustainable architecture has gained increasing attention in response to the ongoing climate crisis. Traditional architecture, which is shaped by local culture, geography, and climate, plays a vital role in maintaining local wisdom and preserving the genius loci. This type of architecture often involves traditional materials and techniques passed down through generations. In Indonesia, traditional houses, such as those found in Pasanggrahan, Purwakarta Regency, West Java, exemplify this approach by reflecting the region’s climate and cultural conditions. Despite their significance, research on traditional Indonesian house architecture remains limited. This study aims to explore the architectural characteristics of houses in Tajur Village, focusing on material use, building and village typology, and how they respond to the local climate. Using a descriptive qualitative method, data was collected through interviews, documentation, and observations. The findings show that Tajur Village homes are highly adapted to the local climate through their materials, design, and structure. These climate-responsive solutions can inspire sustainable architecture that addresses the challenges of climate change.